Contrasting usage of web-based library services among postgraduate students by type of university within Malaysia - Mohd Zain, Wahidah; Othman, Roslina; Mat Ripin, Faizal Hazri (Taylor & Francis, 2016)
This article aims to describe the differences between research-focused and teaching-focused (non-research) universities in terms of usage of web-based library services, as discovered by way of questionnaires and statistical analyses. It was found that the type of university within the country of Malaysia correlates to significant differences in usage of e-journals and Web-based library services in general. Factors such as library budget allocations, research productivity, and extrinsic motivations for using Web-based library services are surmised to have influenced the usage. The results also suggest that library programs at both types of universities are ineffective in creating awareness of the services. This article discusses several aspects of usage in both types of university and makes several suggestions to remedy identified problems.